Mewujudkan Desa Mandiri: FGD Pendataan Lembaga Kemasyarakatan Desa - Sunaryono Sunaryono (Pusat Riset dan Inovasi Nasional, 2024)
The realization of self-reliant villages is a crucial pillar in fostering prosperous and competitive communities amid rapid development. Accurate and comprehensive data management of village community organizations (Lembaga Kemasyarakatan Desa, LKD) is essential for informed decision-making, meticulous planning, and effective program implementation. This article discusses the role of Focus Group Discussions (FGDs) in enhancing LKD data collection processes. FGDs serve as an effective method to gather in-depth information and diverse perspectives from stakeholders, facilitating the identification of needs and challenges, formulation of effective data collection strategies, and fostering commitment and collaboration among participants. The outcomes of these FGDs include more accurate and relevant data, enhanced human resource capacities, and improved village self-reliance. This approach underscores the importance of collective effort and strategic planning in achieving genuine village autonomy, leveraging the spirit of cooperation and collaboration to build resilient and thriving communities